Application of Vermicompost with Different Feeding Material for Inducing Rice Plant Resistance against Brown Planthopper (Nilaparvata lugens Stål.) Attack - Dewi Hastuti; Eltis Panca Ningsih; Sri Ritawati; Rida Oktorida Khastini (Universitas Gadjah Mada, 2021)
Brown planthopper (BPH) is a major pest in rice plants and has become a global pest. This pest causes hopperburn in rice plants. This research aimed to know the effect of vermicompost from different feeding materials on rice plant damage by brown planthopper attack. This research was carried out between November 2019–March 2020 at the Sistandu integrated farming system, Serang City, Banten. The experiment method used in this research was a factorial Randomized Block Design (RBD) and consisted of two factors with three replications. The first factor was vermicompost (P) 5 levels, while the second factor was rice varieties (V) with two groups resulting in ten treatments. Data were analyzed with ANOVA, then followed by a 5% DMRT. The results showed that the application of vermicompost with different feeding materials had non-significant effects on growth of rice plants in the vegetative phase and fecundity of the BPH. However, it significantly affected the intensity of rice plant damage in the generative phase, the offspring population of BPH, and the BPH feeding rate. While the use of two varieties of rice did not have distinct effects on all parameters. There was no interaction effect between the two factors tested, both vermicompost feeding material treatment and rice plant variety, to all the parameters that have been studied.